2010
DOI: 10.1007/s00276-010-0678-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the formation of maxillary sinus in Japanese human foetuses using cone beam CT

Abstract: The formation of the maxillary sinus (MS) is tied to the maturation of the craniofacial bones during development. The MS and surrounding bone matrices in Japanese foetal specimens were inspected using cone beam computed tomography relative to the nasal cavity (NC) and the surrounding bones, including the palatine bone, maxillary process, inferior nasal concha and lacrimal bone. The human foetuses analysed were 223.2 ± 25.9 mm in crown-rump length (CRL) and ranged in estimated age from 20 to 30 weeks of gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…The roots of the posterior teeth are located close to the maxillary sinus floor and can be found outside the maxilla by 30 weeks of gestation. Therefore, the roots of the first and second molars are located in close proximity to the maxillary sinus floor [5].…”
Section: Discussionmentioning
confidence: 99%
“…The roots of the posterior teeth are located close to the maxillary sinus floor and can be found outside the maxilla by 30 weeks of gestation. Therefore, the roots of the first and second molars are located in close proximity to the maxillary sinus floor [5].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, new possibilities and applications for CBCT have arisen in the fields of OMF surgery, dentistry and otorhinolaryngology. Upper airway analysis in particular has become increasingly relevant mainly due to the relationship between morphological airway character- Frankfort plane parallel to the floor 24,67 Natural head position 45,72 Craniocervical inclinations were examined to ensure they were between 908 and 1108 44 Head fixed in the operative position at the centre of the C-arm using a brace 59 After image acquisition, head was oriented so that it was straight with no cant 70 After image acquisition, head was oriented according to a line 68 down from the sella-nasion as the horizontal axis 37 Not specified 2,3,15,29,35,39,47,52,61,64 Not relevant 11,12,18,21,40,43,62,73,75 Mandibular position control…”
Section: Discussionmentioning
confidence: 99%
“…The effects of RPE on the maxilla were studied by one research group 35 who reported a statistically significant increase in nasal width and a decrease in maxillary sinus width. CBCT was also used to investigate the prevalence of sphenoid sinus hypoplasia and agenesis in the Turkish population 17 and the formation of the maxillary sinus in Japanese fetuses 11 .…”
Section: Evaluation Of Sinus Anatomy and Pathologymentioning
confidence: 99%
“…Defining the position of the nasolacrimal sac and duct during this surgical procedure is important. Studies defining the nasolacrimal apparatus in cadavers and in healthy people using computed tomography have been reported in the literature [1,11,15]. McCormick and Sloan [11] measured the diameter of the nasolacrimal canal using computed tomography and analyzed according to gender and racial differences.…”
Section: Introductionmentioning
confidence: 99%